The role of the state in the protection of basic human rights and freedoms - Spruk, Jure (Teorija in praksa, 2022)
The article addresses the question of the role of the state in the protection of human rights and freedoms. Like states, rights and freedoms are also created on the basis of social conventions, and any reference to the universal nature or natural character of rights and freedoms is only an ideological moment in the pursuit of political goals. The basic prerequisite for the protection of rights and freedoms is the establishment of organised coercion in the form of state power which brings under its authority the multitude of different interests and diverse ways of implementing justice. The conclusive findings show that for its successful introduction into the lives of individuals, the moral discourse of universal human rights and freedoms needs effective state authority that embeds these rights and freedoms into the foundations of the legitimacy of its own existence
Keywords: Človekove pravice; človekove svoboščine; država; Svoboda; vloga države; zaščita pravic